Fostering Antifragility: What Policymakers Should Know About Individual Resilience in Romania - Călin Vâlsan; Elena Druică; Paul Dragos Aligică (Administrative Sciences, 2025)
Recent studies document a disappointingly low impact of resilience interventions and policies. This prompts us to revisit the formation of perceived individual resilience using a country-representative sample of 1500 adults. Our study explores how this perception is shaped by family resilience, community resilience, and several control variables like age, gender, risk aversion, and the perception of immediate environmental safety. Unlike traditional methods, we employ the PLS-PM methodology and WarpPLS 7.0 software. Our key findings document non-linear dynamics with varying degrees of magnitude, significance, and effect sizes. The three dimensions of family resilience (social trust, shared beliefs and support, and family organization and interaction) are the most significant predictors of community resilience. These non-linear relationships might explain occasional declines in individual resilience, linking our findings to those of previous studies. We contend that resilience policies and interventions are not unlike risk management, and therefore policymakers should be aware of diminishing marginal returns.